Apakah Kadar Asam Urat Menyebabkan Berkembangnya Prehipertensi Menjadi Hipertensi? - Oktavia, Shanty; Farapti, Farapti (Universitas Batanghari Jambi, 2024)
Hypertension is a health problem that continues to increase in prevalence. Several studies showed that hypertension is related to conditions of oxidative stress which can be caused by increased levels of uric acid in the blood. The aim of this study was to analyze the role of uric acid levels in the development of blood pressure from prehypertension to hypertension. This study is a literature review of the results from cohort studies related to the relationship between serum uric acid levels on the development of prehypertension to hypertension.This study was based on the results of the identification from articles in the Google Scholar with the search keywords â€œUric acid serum predict prehypertension to hypertension cohortâ€ with inclusion criteria such as full text in PDF format, english, and span of the last ten years (2013-2023). There were 3 international journal articles which showed that increased uric acid levels could affect the development of prehypertension blood pressure into hypertension. Blood pressure belonging to prehypertension with hyperuricemia had a greater incidence of hypertension than the group without hyperuricemia (P<0,001). Prehypertension accompanied by hyperuricemia had a 2 times greater risk of developing hypertension within 2 years (OR, 2.02; P<0,05). Increased uric acid levels that occured over time also predicted the development of the prehypertensive blood pressure category to become hypertension independently (OR, 1.41 ; P<0,0001). Based on the results of the literature review, it was concluded that high serum uric acid levels or hyperuricemia is a risk factor for the development of prehypertension to hypertension.